Big data analytics and knowledge discovery : 20th International Conference, DaWaK 2018, Regensburg, Germany, September 3-6, 2018, Proceedings /: 20th International Conference, DaWaK 2018, Regensburg, Germany, September 3-6, 2018, Proceedings. (2018) - Unknown
No abstract available